"Midwives need a museum": What can the experience of the Midwife Museum teach us? (Cadernos de Sociomuseologia, 2025)
AbstractThe Museu da Parteira arises from the desire of traditional midwives from Pernambuco, a state in northeastern Brazil, after a research process focused on the patrimonialization of the profession that mobilized midwives and communities. The article analyzes the historical and political context of its emergence, as well as the trajectory of the museum, pointing out the paths taken and the contributions brought to the field of museums.Key Words: Midwife; Heritage; Museum